Grazing Behavior in Ungulates: Current Concepts and Future Challenges - Vavra, Martin; Ganskopp, David (Annals of Arid Zone, 2016)
An early focus on ungulate foraging behavior occurred in the 1940’s as scientists began quantifying the activities of livestock and wildlife to address production goals. Interest resurfaced in the 1970’s and continued as investigators pondered behavior related hypotheses at evolutionary, ecosystem. and plant/animal interface levels. Presently, many grazing land environmental concerns are related to the selective foraging habits of ungulates and their poor distribution about the landscape. These two facets of ungulate behavior serve as the impetus for many of today’s research efforts, and scientists in the field need to develop a theoretical framework to address these problems. The theories of optimum foraging and adaptive rumen (unction were offered to explain evolutionary patterns of forage selection among herbivores, but they lack the specificity needed by range and pasture managers at relevant space and time scales. While post-ingestive feedback mechanisms cause aversions to toxic plants, and some species of herbivores have developed means of neutralizing harmful compounds, the mechanisms stimulating the development of forage preferences in the absence of aversive compounds are not clearly understood. Ungulates also exhibit selective patterns of spatial use about the landscape. In some environments where necessary resources (water, shade, forage. minerals, escape topography or cover) are scarce, areas of activity will be focused about these limiting elements. Many of the herding ungulates, however, repeatedly regraze certain areas and avoid other equally suitable portions of the landscape. Research suggests these habits elevate the animal’s nutritional status by curtailing advances in plant phenology and removing the hindrances of cured forage from the grazed patches. Such a scenario increases landscape diversity and may enhance species richness and accelerate nutrient cycling in the grazed areas by maintaining vegetation in an earlier stage of succession. Recent investigations suggest that ungulates can retain and use spatial memory to expedite foraging, and can associate shapes and colors with the presence or absence of food. These skills have been clearly demonstrated in small, well controlled environments, but patterns of behavior and distribution in extensive landscape settings are poorly understood. The recent advances in geographic information systems and global positioning systems will assist us greatly in our analyses of ungulate behavior at landscape levels of resolution. Pasture and landscape managers are beginning to recognize many of the innate habits and preferences of livestock though, and are exploiting these behaviors to affect plant succession, control weeds, and manipulate forage quality or structure of the plant community. There is much left to learn. but as we make inroads in these endeavors, the value of grazing animals can only increase.